PENGGUNAAN SINAR INFRA MERAH UNTUK DETEKSI PANAS BUMI DAERAH SANGKANHURIP, KUNINGAN, JAWA BARAT - Sumotarto, Untung; Hendrasto, Fajar; Anugrahadi, Afiat; Purwiyono, Taat Tri; Ashari, Wahyu Robiul (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2024)
Geothermal resources can be explored with aerial photographs followed by surveys and analysis of geological, geochemical and geophysical data as well as shallow drilling. This research was conducted to determine the potential of geothermal resources using a camera capable of capturing infrared rays from objects and photo targets.Geothermal exploration is generally carried out with an initial survey using remote imagery and aerial photography techniques. Taking photos using a tool equipped with a Thermal Infrared Sensor (TIRS), namely a camera equipped with Forward Looking InfraRed (FLIR).The initial survey in this study was conducted at five locations of geothermal springs in the Sangkanhurip area, Kuningan, West Java. From these five locations using FLIR cameras detected geothermal resources with hot spring temperatures between 30 to 40 degrees Celsius.To find out the types of rocks that exist, a geological survey was carried out to make a geological map. The data and information obtained are then analyzed to obtain a map that displays geology with surface temperature data in the study area.This map can be utilized by companies interested in exploring and producing geothermal energy for use as a source of energy for Geothermal Power Generation (PLTP). Further analysis can be carried out with the Geochemical Method for predicting subsurface temperature. This discovery fulfills the research objective of detecting geothermal resources using infrared rays.